Improving the Definition of the Notion “Goods” for Accounting Purposes of Trade Enterprises - Olshanska, M. V.; Fal, Yu. Ya. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
Trade as a type of activity is carried out by the majority of enterprises, both in Ukraine and abroad. Trade in Ukraine was rapidly growing in 2012–2017, with re-orienting to EU markets, which modifies the requirements to goods, approaches to their management and accounting. This raises the importance of theoretical studies associated with interpretation of the notion “goods”. The article aims to propose an optimized definition of “goods” for accounting purposes of trade enterprises by making a review of the existing approaches to this category definition, found in theoretical studies and normative documents. A review of theoretical and normative sources shows the lack of agreement in the interpretation of “goods” that tend to be addressed by researchers from broader (economic) and narrower (accounting) perspective. The definition of “goods” for accounting purposes of trade enterprises is, therefore, optimized by summing up theoretical definitions of “goods” and interpretations of the notions “sales”, “distribution”, “exchange”, and “profit”. It is justified that to be recognized as a good, an asset must be reliably measured. It is also proposed to use a more comprehensive notion “exchange” in place of “sales” or “distribution”, and “obtain an economic benefit” in place of “obtain a profit”. The resulting definition of “goods” is: “Assets (excluding money), which value is reliably defined, which are supposed to be used for further exchange in order to obtain an economic benefit, and which main purpose is to meet consumer demand”.